2020
DOI: 10.1177/2158244020926570
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Middle School Students’ Engagement Through Incorporating iPad Apps in EFL/ESL Classes

Abstract: The use of iPad and other handheld devices in classrooms is spreading. Their use can empower learners and expose them to a plethora of resources. Yet, when it comes to learning a foreign language, reasonably little has been done to empirically ascertain the influence of iPad apps on facilitating language learning as well as engaging language learners. Thus, this study endeavored to illumine the extent to which a selection of iPad applications, used as a pedagogical tool, augment young learners’ engagement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…According to Elyas, regarding the current educational shift 'the Ministry of Education was in a dilemma. However, remarkably they managed to control the situation by introducing the new official way of learning and creative way of online learning [4]. The first step towards this significant shift has been to design a platform to ensure continuity in learning.…”
Section: Introductionmentioning
confidence: 99%
“…According to Elyas, regarding the current educational shift 'the Ministry of Education was in a dilemma. However, remarkably they managed to control the situation by introducing the new official way of learning and creative way of online learning [4]. The first step towards this significant shift has been to design a platform to ensure continuity in learning.…”
Section: Introductionmentioning
confidence: 99%
“…The teacher's role in online teaching both 'during COVID-19' and 'before the pandemic' is not merely to present the material, but rather to introduce students to creative methods [8], where the physical interaction is missing. Hence, the role would need to change from being authoritative to a cooperative, engaging, playful, and fun learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the role would need to change from being authoritative to a cooperative, engaging, playful, and fun learning environment. In a cooperative classroom, teachers are part of an interactive environment that focuses on aural and visual stimulation [8]. Students become creators, shaping their own experiences independently and actively contributing to the shape of the classroom's environment through visual and aural manipulation, while the teacher would act as a creative guide who enhances their experiences through feedback [8].…”
Section: Introductionmentioning
confidence: 99%
“…Educators should therefore integrate digital tools as a way for students to learn, rehearse, and master the content on their own, further promoting active learning. A research by Al-Bogami and Elyas (2020) found that the use of iPad applications like Quizlet for reading activities made students enjoy the lessons more and has positive impacts on the students' motivation, focus and engagement. Although the features in Quizlet (e.g.…”
Section: Discussion and Pedagogical Implicationsmentioning
confidence: 99%